(untitled) (Revista Sistemas de Producción Agroecológicos, 2013)
Natural resources are the elements and forces of nature that man can use and benefit and also represent sources of wealth for economic exploitation. But the best use of a resource depends on the knowledge that man has on the laws governing the conservation of natural resources. Sustainable management is a global concern and food production is a fundamental basic need to ensure food security and sovereignty of the people of a territory, by which great importance is the rational use of land and water. Currently it appears that the main aim of human when landless is exploitation, is the rapid economic gains that guarantee a quality of life than man has, relegating the appropriate land use, this means that in Colombia on the total land used in severe and moderate degree is over 60%, especially in agricultural activities in areas recommended for forest protection and production in order to achieve comprehensive conservation and restoration of water resources. Farmers in Colombia are used to being surrounded by a large biodiversity, enjoying an optimal environment where you can get any agricultural product, and will always consider these benefits, leading to irrational management, resulting in landscape desertification, eroding soils, depletion of wildlife, watershed pollution, causing socioeconomic poverty uncontrollable due to an imbalance in the environment, with the fear that these processes are difficult or irreversible recovery. The paper concludes with the solutions that have been proposed environmental entities and as citizens agricultural professionals can provide support to contribute to the better management and conservation of the most important resource, but also the most forgotten "SOIL".